2012
DOI: 10.1111/j.1749-6632.2012.06759.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition receptors and their role in invasive aspergillosis

Abstract: Pattern recognition receptors (PRRs) are germline receptors that recognize conserved structures on microorganisms. Several PRRs have been identified in the recent years that are involved in the immune response against Aspergillus fumigatus. The role of PRRs in invasive pulmonary aspergillosis becomes especially apparent in the setting of an immunocompromised status of the host because of the redundancy of many PRRs in the host defense against A. fumigatus. Studies that investigated the PRRs and their effector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Aspergillus-induced IL-5 and IL-13 response is dependent on complement receptor 3 and phagocytosis As most PRRs have been studied in the context of invasive aspergillosis [3], only little is known about the PRRs and pathways involved in the pathogenesis of ABPA. We investigated the role of TLR2, TLR4, dectin-1 and complement receptor 3 (CR3) pathways in Aspergillus-induced Th2 responses in human PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus-induced IL-5 and IL-13 response is dependent on complement receptor 3 and phagocytosis As most PRRs have been studied in the context of invasive aspergillosis [3], only little is known about the PRRs and pathways involved in the pathogenesis of ABPA. We investigated the role of TLR2, TLR4, dectin-1 and complement receptor 3 (CR3) pathways in Aspergillus-induced Th2 responses in human PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the role of two PRRs during the phagocytic process of L. prolificans by microglia, MR and dectin‐1, was evaluated. These receptors have been described previously as very important during the recognition of fungal pathogen‐associated molecular patterns and are involved in the recognition of N ‐linked mannans and β‐glucans, respectively (Gresnigt, Netea, & Van de Veerdonk, ; Netea, Brown, Kullberg, & Gow, ). Interestingly, we showed that both PRRs were mediating L. prolificans conidia uptake by microglial BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators measuring cytokine levels were blinded towards classification of cases into IPA categories and all other clinical and demographic information. The 11 cytokines in the immunoassay were selected based on published literature in human and animal models showing an increase or decrease of these cytokines in blood and/or BALF of cases with IPA . The cytokines studied were: interleukin (IL)‐4, IL‐6, IL‐8, IL‐10, IL‐15, IL‐17A, IL‐22, soluble IL‐2 receptor (sIL‐2r), tumours necrosis factor (TNF) α, interferon (IFN) γ and RANTES (chemokine ligand 5).…”
Section: Methodsmentioning
confidence: 99%